Proses Pemberdayaan Ibu-Ibu Rumah Tangga oleh Bank Sampah “Kebumen Gemilang ‎Sejahtera” di Kelurahan II Ilir Kecamatan Ilir Timur II Kota Palembang - Sumantri, Hamdani; Yunindyawati, Yunindyawati; Suleman, Zulfikri (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
Women's empowerment is a good step to develop and improve women's competencies, especially for ‎housewives. This research examines the process of community empowerment in recycled waste ‎management in Kelurahan II Ilir, with a focus on the Kebumen Gemilang Sejahtera (KGS) Waste Bank. ‎There are five main processes observed, namely enabling, strengthening, protecting, supporting, and ‎maintaining which are used to create a supportive climate, increase knowledge and skills, and encourage ‎community independence and innovation in waste management for housewives. The method used is ‎analytic descriptive qualitative method. The qualitative research method is considered capable of describing ‎the process of empowering housewives by the KGS Waste Bank. As a result, the community, especially ‎housewives, managed to develop skills in waste management, become independent and innovative, and can ‎spread their knowledge to other parties. This empowerment program has succeeded in creating a positive ‎impact in protecting the environment and improving the welfare of the community.